Real ear unaided gain and its relation with the equivalent volume of the external and middle ear - Bastos, Bárbara Guimarães; Ferrari, Deborah Viviane; Blasc, Wanderléia Quinhoneiro (International Archives of Otorhinolaryngology, 2012)
Introduction: Old age is associated with changes in the characteristics of the middle ear transmission system and in external ear resonance, and these carry implications for the hearing aid (HA) verification process for which targets and measures of the real ear insertion gain (REIG) are used.Aim: To compare the real ear unaided gain (REUG) and the equivalent volumes of the external ear (VeqEE) and the middle ear (VeqME) between elderly and adult patients.Methods: This is a retrospective study in which the medical records of 28 elderly patients (aged between 61 and 102 years, average hearing thresholds between 38.75 and 85 dB HL) and 23 adult patients (aged 20–59, mean hearing thresholds between 31.25 and 116.25 dB HL) with bilateral sensorineural hearing loss and no history of middle ear abnormalities were analyzed. Immittance measurements (VeqEE, VeqME, and pressure of the peak of maximum compliance) and the REUG (frequency and amplitude of the primary peak) were recovered for a total of 40 ears. These data were compared between elderly and adults as well as between men and women, using Student's t test. Correlations (Pearson) between immittance and REUG data were also verified.Results: No statistically significant differences (p < 0.01) were found for immittance and REUG data between elderly and adults, or between men and women. A negative and weak but significant correlation was observed between the REUG primary peak and VeqEE.Conclusion: Hearing aid verification can be performed with target and measures of the REIG in the elderly population.
Keywords: audiology; acoustic impedance tests; ear; external; ear; middle; aged